Calcium Supplements and Risk of Cardiovascular Disease: A Meta-Analysis of Clinical Trials - Seung‐Kwon Myung; Hong-Bae Kim; Yong‐Jae Lee; Yoon‐Jung Choi; Seung‐Won Oh (2021)
Recent systematic reviews and meta-analyses of randomized, double-blind, placebo-controlled trials (double-blind, placebo-controlled RCTs) have reported controversial findings regarding the associations between calcium supplements on the risk of cardiovascular disease (CVD). This meta-analysis aimed to investigate the association between them.We searched PubMed, EMBASE, the Cochrane Library, and the bibliographies of relevant articles for double-blind, placebo-controlled RCTs in November, 2020. Relative risks (RRs) with 95% confidence intervals (CIs) for the risk of cardiovascular disease were calculated using a random effects model. The main outcomes were CVD, coronary heart disease (CHD), and cerebrovascular disease.A total of 13 double-blind, placebo-controlled RCTs (n = 28,935 participants in an intervention group and 14,243 in a control group)) were included in the final analysis. Calcium supplements significantly increased the risk of CVD (RR 1.15, 95% CI 1.06-1.25], I2 = 0.0%, n = 14) and CHD (RR 1.16, 95% CI 1.05-1.28], I2 = 0.0%, n = 9) in double-blind, placebo-controlled RCTs, specifically in healthy postmenopausal women. In the subgroup meta-analysis, dietary calcium intake of 700-1000 mg per day or supplementary calcium intake of 1000 mg per day significantly increased the risk of CVD and CHD.The current meta-analysis found that calcium supplements increased a risk of CVD by about 15% in healthy postmenopausal women.